Experimental culture of Basidiomycetes causing white rot fungi of the Amazon region in different substrates - Sales-Campos, Ceci; da Silva Pessoa, Leise; de Jesus, Maria Aparecida; Helm, Cristiane Vieira; Martins, Olívia Gomes [UNESP]; Andrade, Meire (Centro Universitario de Maringa, 2022)
Technology for the culture of fungi in the Amazon region is highly deficit, even though the region has great potentiality. Current study analyzes the experimental production of new strains of Amazon basidiomycetes at different substrates and temperatures. Fungus strains, Pleurotus ostreatus, Boletus sp., Agaricales, Auricularia sp., Pleurotus djamor var. roseus and Agaricomycetes were retrieved from the laboratory for the Culture of Eatable Fungi of COTI/INPA. Prime matter for the preparation of the substrate were wood wastes: marupá (Simarouba amara) and cajuí (Anacardium giganteum), and agroindustrial wastes: pseudostem of the banana tree (Musa sp.) of the variety Thap Maeo. Randomized assay design comprised a factorial scheme 4 x 6 x 2 (4 substrates, 6 strains and 2 temperatures), with 3 replications each, totaling 144 experimental units. Mycelial growth was measured daily, at two temperatures (25 and 30°C), till total colonization of substrates by the fungi. Loss of organic matter (LOM %) was also evaluated. Data underwent analysis of variance ANOVA, and means compared by Tukey's test (5%). In most treatments polynomial lines showed a similar growth with hikes in some cases. In the case of LOM PMO (%), substrate of cajuí, Thap Maeo and mixture of bran had the highest rates. The two temperatures were positive for the strains development. All strains investigated had an affinity by tested substrates in vitro and could be employed in further studies.
Cultivo experimental de Basidiomicetos causadores de podridão branca da região Amazônica em diferentes substratos
Keywords: Fungi; Mycelial growth; Sawdust; Temperature